Penanaman Nilai Creative Thingking Melalui Konsep Character Building pada Anak di Rumah Pintar YAFSI - Vellin Syahya Jingga; Husni Thamrin (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Drawing is a means of expression, development of activities, depicting imagination and fantasy, which are very important in maintaining the development and growth of children’s creativity and productivity. Drawing is also one of the parts in seeking identity beacuse children feel they can be honest and independent from the demands that surround them. The purpose of this paper is as a result of the author's dedication in developing children's creative thinking at the Rumah Pintar YAFSI. The method used is qualitative research with data collection techniques by observation. In this casework activity, the writer took one of the children to help increase their creative potential through drawing and story telling. Children's abilities are not only measured by the limits of numbers and letters which have been the main focus in learning. Children's motor skills and imagination must also be included in the attention of learning.